IMPLEMENTASI MEDIA PEMBELAJARAN BERBASIS ANDROID TERHADAP HASIL BELAJAR BAHASA INDONESIA - Nur indah; Kasman Kasman (Akademika : Jurnal Teknologi Pendidikan, 2021)
The purpose of this study was to determine the effect of the implementation of Android-based learning media on students' learning outcomes of Indonesian at SMA Muhammadiyah Unismuh Makassar. The method used in this research is quantitative descriptive research method. The population in this study were all students at SMA Muhammadiyah Unismuh Makassar as many as 388 students. The sample in this study was 49 students. The data collection instruments used in this study were questionnaires and tests. The data analysis technique used in this research is quantitative descriptive analysis using the product moment correlation formula. The results showed that the r-count value, which is 0.998, is greater than the rtab, which is 0.281, so the alternative hypothesis (Ha) is accepted and nil (Ho) is rejected. The results showed that if the Android-based media was used according to the portion needed in the learning process and following the instructions from the educator, in this case the teacher of the Indonesian Bahasa subject, it would have a positive impact on student learning outcomes. It can be concluded that there is a significant influence between the implementation of android-based learning media with the learning outcomes of Indonesian students at SMA Unismuh Makassar.